Implementasi Pasal 4 Peraturan Daerah Kabupaten Lampung Utara Nomor 02 Tahun 2017 tentang Pengelolaan Sampah di pasar bukit kemuning: Analisis Siyasah Tanfidziyah di Dinas Lingkungan Hidup Kabupaten Lampung Utara - Diana Novita Sari; Iskandar Syukur; Edi Susilo (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine the implementation of Article 4 of the North Lampung Regency Regional Regulation Number 02 of 2017 concerning waste management in Bukit Kemuning Market from the perspective of siyasah tanfidziyah. The focus of this research lies in the implementation of policies by the Environmental Agency of North Lampung Regency as the executive institution responsible for realizing public welfare through waste management. This study employs a qualitative approach using field research methods. Data collection techniques were conducted through interviews, observations, and documentation involving informants from the Environmental Agency, the Head of Bukit Kemuning District, Uberli (Environmental Cleanliness Unit) and market traders. The results of the study indicate a gap between the provisions of the regional regulation and its implementation in the field. This is reflected in the accumulation of waste, the low awareness of the community and traders in maintaining cleanliness, and the limited waste management facilities and infrastructure. The main inhibiting factors include insufficient budget allocation, the absence of temporary waste disposal sites (TPS), and the limited number of waste transportation vehicles. From the perspective of siyasah tanfidziyah, this policy implementation has not fully reflected Islamic values because the local government, as ulil amri, has not optimally carried out its mandate to achieve public welfare